2005
DOI: 10.1080/10519990500048611
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and psychometric properties of the Frost Multidimensional Perfectionism Scale: Developing shorter versions using an Australian sample

Abstract: The factor structure, psychometric properties and clinical utility of the Multidimensional Perfectionism Scale (FMPS) developed by Frost, Martin, Lahart, and Rosenblate (1990) is investigated for the first time on the basis of an Australian sample. Consistent with recent studies, four dimensions instead of the original six emerged as a result of exploratory factor analysis. Retaining 24 items out of the original 35 items refined the scale. This brief version is referred to as FMPS-24 item. Further investigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(65 citation statements)
references
References 38 publications
2
61
0
2
Order By: Relevance
“…Given that a variety of factor structures have been found for the Frost perfectionism measure (22)(23)(24)(25)(26)(27), the four scales measuring temperament were used as originally proposed (22), as this is the format most commonly used in the examining the relationship between perfection and eating disorders and thus makes our results comparable with other studies. The two scales that report retrospectively on parental criticism and expectations were not used.…”
Section: Self-report Measuresmentioning
confidence: 93%
“…Given that a variety of factor structures have been found for the Frost perfectionism measure (22)(23)(24)(25)(26)(27), the four scales measuring temperament were used as originally proposed (22), as this is the format most commonly used in the examining the relationship between perfection and eating disorders and thus makes our results comparable with other studies. The two scales that report retrospectively on parental criticism and expectations were not used.…”
Section: Self-report Measuresmentioning
confidence: 93%
“…Note that some additional studies with the FMPS were not included in Table 6.1 because they focused on total perfectionism scores and established a strong, positive link between total FMPS scores and scores on the PSWQ (e.g., Smári, Olason, Eypórsdóttir, & Frölunde, 2007;Whiting et al, 2014) or they combined the FMPS dimensions into composite scores, but with a nonstandard version of the FMPS. For instance, Khawaja and Armstrong (2005), as part of their attempt to reduce the FMPS to 24 items, showed that PSWQ scores were linked robustly with a factor that combined COM and DAA ( r = .56) and there was also a significant correlation between worry and the PS factor ( r = .28).…”
Section: Research On Perfectionism and Worrymentioning
confidence: 99%
“…The same conclusion was reached by Anshel and Seipel (2006) who conducted a confirmatory factor analysis of the item responses of 186 undergraduates. Khawaja and Armstrong (2005) suggested that the FMPS could be reduced to 24 items but their analyses with data from an Australian sample yielded only four factors.…”
Section: Construct/factor Analyticmentioning
confidence: 99%